Question and Answers Forum

All Questions      Topic List

Number Theory Questions

Previous in All Question      Next in All Question      

Previous in Number Theory      Next in Number Theory      

Question Number 207423 by efronzo1 last updated on 14/May/24

    ⇃

$$\:\:\:\:\downharpoonleft\underline{\:} \\ $$

Answered by mr W last updated on 14/May/24

let a_n =b_n +k  b_(n+1) +k=−(2/3)+2b_n +2k  b_(n+1) =2b_n +k−(2/3)  set k−(2/3)=0, i.e. k=(2/3)  b_n =2b_(n−1) =2^2 b_(n−2) =...=2^(n−3) b_3          =2^(n−3) (a_3 −k)=2^(n−3) (2−(2/3))=(2^(n−1) /3)  ⇒a_n =b_n +k=(2^(n−1) /3)+(2/3)  ....

$${let}\:{a}_{{n}} ={b}_{{n}} +{k} \\ $$$${b}_{{n}+\mathrm{1}} +{k}=−\frac{\mathrm{2}}{\mathrm{3}}+\mathrm{2}{b}_{{n}} +\mathrm{2}{k} \\ $$$${b}_{{n}+\mathrm{1}} =\mathrm{2}{b}_{{n}} +{k}−\frac{\mathrm{2}}{\mathrm{3}} \\ $$$${set}\:{k}−\frac{\mathrm{2}}{\mathrm{3}}=\mathrm{0},\:{i}.{e}.\:{k}=\frac{\mathrm{2}}{\mathrm{3}} \\ $$$${b}_{{n}} =\mathrm{2}{b}_{{n}−\mathrm{1}} =\mathrm{2}^{\mathrm{2}} {b}_{{n}−\mathrm{2}} =...=\mathrm{2}^{{n}−\mathrm{3}} {b}_{\mathrm{3}} \\ $$$$\:\:\:\:\:\:\:=\mathrm{2}^{{n}−\mathrm{3}} \left({a}_{\mathrm{3}} −{k}\right)=\mathrm{2}^{{n}−\mathrm{3}} \left(\mathrm{2}−\frac{\mathrm{2}}{\mathrm{3}}\right)=\frac{\mathrm{2}^{{n}−\mathrm{1}} }{\mathrm{3}} \\ $$$$\Rightarrow{a}_{{n}} ={b}_{{n}} +{k}=\frac{\mathrm{2}^{{n}−\mathrm{1}} }{\mathrm{3}}+\frac{\mathrm{2}}{\mathrm{3}} \\ $$$$.... \\ $$

Answered by AliJumaa last updated on 15/May/24

i have been derrived this form :    { ((u_(n+1) =au_n +b)),((u_m =k)) :}  ⇒ u_n =a^n (((k+(b/(a−1)))/a^m ))−(b/(a−1))  a_n =2^n (((2−(2/3))/8))+(2/3)=2^n ((1/6))+(2/3)  1:a_5 =2^5 ((1/6))+(2/3)=6      FALS  2: a_n  ≩0 ∀n∈N       TRUE  i will complete next time

$${i}\:{have}\:{been}\:{derrived}\:{this}\:{form}\::\: \\ $$$$\begin{cases}{{u}_{{n}+\mathrm{1}} ={au}_{{n}} +{b}}\\{{u}_{{m}} ={k}}\end{cases} \\ $$$$\Rightarrow\:{u}_{{n}} ={a}^{{n}} \left(\frac{{k}+\frac{{b}}{{a}−\mathrm{1}}}{{a}^{{m}} }\right)−\frac{{b}}{{a}−\mathrm{1}} \\ $$$${a}_{{n}} =\mathrm{2}^{{n}} \left(\frac{\mathrm{2}−\frac{\mathrm{2}}{\mathrm{3}}}{\mathrm{8}}\right)+\frac{\mathrm{2}}{\mathrm{3}}=\mathrm{2}^{{n}} \left(\frac{\mathrm{1}}{\mathrm{6}}\right)+\frac{\mathrm{2}}{\mathrm{3}} \\ $$$$\mathrm{1}:{a}_{\mathrm{5}} =\mathrm{2}^{\mathrm{5}} \left(\frac{\mathrm{1}}{\mathrm{6}}\right)+\frac{\mathrm{2}}{\mathrm{3}}=\mathrm{6}\:\:\:\:\:\:\mathcal{FALS} \\ $$$$\mathrm{2}:\:{a}_{{n}} \:\gneqq\mathrm{0}\:\forall{n}\in\mathbb{N}\:\:\:\:\:\:\:\mathcal{TRUE} \\ $$$${i}\:{will}\:{complete}\:{next}\:{time} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com